Moving beyond animal models: enriched environments and human substance use disorders - Barillot, Lila; Chauvet, Claudia; Chauchard, Emeline; Besnier, Marc; Harika-Germaneau, Ghina; Noël, Xavier; Jaafari, Nemat; Solinas, Marcello; Chatard, Armand (Frontiers in Behavioral Neuroscience, 2025)
BackgroundPreclinical studies have shown that exposure to a multisensory, stimulating environment (environmental enrichment, EE) can prevent the development of addictive behaviors and reduce the risk of relapse in animal models. However, the extent to which these preclinical findings apply to human addiction remains largely unknown. In this research, we investigated the role of EE in human substance use disorders (SUDs).MethodsA new self-report measure of perceived EE was developed to test, in human participants, whether EE is associated with lower levels of SUD. This scale was administered to two distinct groups: regular smokers (N = 286) and patients diagnosed with severe alcohol use disorder (N = 52). Smokers also provided demographic information and data on nicotine use, while patients with alcohol use disorder reported pre-hospitalization drug intake, detoxification history, and levels of depression and anxiety.ResultsThe EE scale demonstrated adequate psychometric properties, including a stable factorial structure and high test–retest reliability over 1 month. Among smokers, higher scores were significantly associated with lower nicotine consumption, dependence and craving. In patients with alcohol use disorder, lower scores were linked to a history of more frequent relapse. These effects were independent from depression and anxiety.ConclusionEnvironmental enrichment, as perceived and self-reported by individuals, appears to be a promising construct for understanding vulnerability and resilience in human addiction. The scale may serve as a valuable translational tool between preclinical and clinical models, with potential implications for the development of new intervention strategies for SUD.